Sense and Separability: Clarifying Star Athletica Amongst Lower Court Confusion - Curran, Collier N. (The Columbia Journal of Law & the Arts, 2025)
Copyright law is designed to protect the artistic, the creative. For centuries, courts have been careful to avoid granting copyright protection to systems or processes better suited to patent protection. For instance, in a book explaining how to build a house, the text of the book as creative expression would be copyrightable. However, copyright protection would not extend to the actual system or process for building the house. This idea-expression dichotomy becomes more complicated in cases of useful articles with design elements. In the 1954 case Mazer v. Stein, the Supreme Court first addressed the need to physically and/or mentally separate the utilitarian and ornamental elements to determine which aspects, if any, may be copyrighted. This case led to the codification of separability in the Copyright Act of 1976; § 101 requires that a copyrightable pictorial, graphic, and sculptural work (“PGS work”) contain “sculptural features that can be identified separately from, and are capable of existing independently of, the utilitarian aspects of the article.” Despite this attempt at clarification, a nine-way circuit split emerged, with courts— as well as the Copyright Office itself—taking various approaches to the separability analysis. In fact, the Second Circuit developed three different approaches itself, each attempting to identify the supremacy of the artistic or creative elements over the utilitarian aspects of a work in order to award it copyright protection.